In vivo Toxicological Assessment of the Aqueous Extracts of the leaves of carissa edulis (Apocyanaceae) in Wistar Rats - Osseni, Razack; AKOHA, STEPHEN; ADJAGBA, Marius; AZONBAKIN, AZANDÉGBÉ SIMON; LAGNIKA, LATIFOU; AWEDE, BONAVENTURE L. SÉVERIN; BIGOT, KOFFI ANDRÉ; ADAMOU, Diouf; DARBOUX, RAPHAËL BARTHÉLÉMY; LALEYE, OLABISSI ANATOLE A. (My University, 2016)
Aim: To screen the acute and 28-days subchronic toxicity of the leaves aqueous extract of Carissa edulis (C. edulis). Design: Experimental and observational study. Place and Duration: Faculty of health sciences of Cotonou / Institute of Applied Biomedical Sciences of Cotonou, laboratories of Physiology/Human biology/Immunology/ biochemistry and molecular biology( pharmacognosy section) / toxicology and hydrology of Dakar (Senegal) between March 2014 and January 2015. Methods: The aqueous extract was obtained from the powder of the leaves by a decoction method and evaporation using a rotavapor. In the acute toxicity study (Limit test), a single dose of 2000 mg/kg of the extract was orally administered to three female rats. Different parameters were assessed according to the Organisation for Economic Co-operation and Development (OECD) 423 guidelines for the Testing of Chemicals. During the sub-chronic toxicity, four groups of five rats of either sex received distilled water (control), 31.25,125 and 500 mg/kg of the extract daily for 28 consecutive days by oral gavage. The assay was conducted according to the OECD 407 guidelines. Results: In both acute and sub-chronic toxicity test, neither mortality nor other toxicity symptoms were observed. This suggests that the median Lethal Dose 50 (LD50) is superior to 2000 mg/kg. There were no significant differences in the body and organ weights between controls and treated animals of both sexes. Indeed, some biological parameters including erythrocytes (6,89±0,07), Haematocrit (41,6±1,69), and Haemoglobin (13,31±0,16) levels were significantly reduced when compared to the control group but this is not imputable pathologically. Histological structures of liver and kidney were normal in both two sexes. Conclusion: The aqueous extract of C. edulis was found to be safe in acute and 28-days subchronic toxicity studies. Furthermore, aspects of the effects of this plant on haematopoiesis, liver and kidney function need to be gained and ascertained over longer periods of toxicity study.
Keywords: Carissa edulis; toxicity; Wistar rats; LD50.